Coping strategies and characteristics of the nursing staff of a private hospital - Benetti, Eliane Raquel Rieth; Stumm, Eniva Miladi Fernandes; Weiller, Teresinha Heck; Batista, Karla de Melo; Lopes, Luis Felipe Dias; Guido, Laura de Azevedo (Rev Rene, 2015)
Objective: to analyze the relationships between sociodemographic/functional characteristics and the coping strategies used by the nursing staff of a private hospital. Methods: it is a quantitative, analytical and cross-sectional study developed with 209 nursing workers. Data were collected sociodemographic/functional characterization and form inventory of the coping strategies. Results: positive reassessment, social support and problem solving were the most used coping factors. There was statistically significant difference between self-control and sex; social support and salary range; acceptance of responsibility and the variables age, number of children, training and salary. The staff use strategies focused on emotions and problems to cope with or to minimize stressors at work. Conclusion: educational activities need to be encouraged aiming to instrumentalize them to do the evaluation of stressors and to use resolutive coping strategies.